(untitled) (Journal of Universal Science Research, 2024)
This article explores the pillars of the global standard of accounting, emphasizing their significance, evolution, and key components. It discusses the importance of a unified standard in facilitating international trade and investment, the historical context of accounting standards convergence, and the role of organizations like the International Accounting Standards Board (IASB) in developing International Financial Reporting Standards (IFRS). Additionally, it highlights challenges and future directions in achieving uniformity across jurisdictions.